2021
DOI: 10.1038/s41467-021-24564-0
|View full text |Cite
|
Sign up to set email alerts
|

Engineered macrophages as near-infrared light activated drug vectors for chemo-photodynamic therapy of primary and bone metastatic breast cancer

Abstract: Patients with primary and bone metastatic breast cancer have significantly reduced survival and life quality. Due to the poor drug delivery efficiency of anti-metastasis therapy and the limited response rate of immunotherapy for breast cancer, effective treatment remains a formidable challenge. In this work, engineered macrophages (Oxa(IV)@ZnPc@M) carrying nanomedicine containing oxaliplatin prodrug and photosensitizer are designed as near-infrared (NIR) light-activated drug vectors, aiming to achieve enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 65 publications
0
90
0
Order By: Relevance
“…Cha et al similarly targeted EGFR by encoding a secreted single-chain variable fragment (scFv) fused to a Fc moiety, which opsonized tumor cells and induced antibody-dependent cellular phagocytosis (ADCP) by macrophages (49). Notably, engineered macrophages can deliver cargo other than genetically encoded proteins; for example, Huang and colleagues used nanoparticles to engineer macrophages that carry photo-sensitive cytotoxic agents, which are released and induce immunogenic cell death upon exposure to near infrared light (51).…”
Section: Reprogramming Macrophages For Tumor Suppression With Cellular Engineeringmentioning
confidence: 99%
“…Cha et al similarly targeted EGFR by encoding a secreted single-chain variable fragment (scFv) fused to a Fc moiety, which opsonized tumor cells and induced antibody-dependent cellular phagocytosis (ADCP) by macrophages (49). Notably, engineered macrophages can deliver cargo other than genetically encoded proteins; for example, Huang and colleagues used nanoparticles to engineer macrophages that carry photo-sensitive cytotoxic agents, which are released and induce immunogenic cell death upon exposure to near infrared light (51).…”
Section: Reprogramming Macrophages For Tumor Suppression With Cellular Engineeringmentioning
confidence: 99%
“…One source is primary macrophages, such as bone marrow-derived macrophages, alveolar macrophages, and peritoneal macrophages. The second source is cell lines, including the mouse macrophage cell lines RAW264.7 and J774A.1 and the human peripheral blood monocyte cell line THP-1 (24,41,(88)(89)(90)(91). NPL-Ms can carry a variety of NPs, including liposomes (92,93), magnetic NPs (94,95), polymeric NPs (96,97), gold (AU) NPs (98)(99)(100)(101), and others (102,103).…”
Section: Engineering Macrophages For Np Delivery In Cancer Therapy Np Loading In Macrophagesmentioning
confidence: 99%
“…Many studies have demonstrated that NP-loaded macrophages (NPL-Ms) can directionally migrate to tumors and transport the payload to tumor cells, leading to a pronounced antitumor effect (39,40). Moreover, after reaching tumors, these engineered macrophages can exert additional effects by stimulating anticancer immune responses (24,41). In this review, we first introduce the origin, differentiation, and function of macrophages as well as the application of nanotechnology in anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the loaded drugs can be released in response to either endogenous or exogenous stimuli [89]. Cells that have been reported for use as nanomaterial carriers include stem cells [90], leukocytes [91], red blood cells [92], and T cells [93]. Methods of endogenous stimulation include pH, reactive oxygen species (ROS), enzyme, hypoxia and so on [94].…”
Section: Nature Cellmentioning
confidence: 99%